Konsep Aqal Dalam Alquran dan Relevansinya dengan Pendidikan Islam - Shelly Alvareza Zazkia (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
The Concept of Aqal in the Qur'an and its Relevance to Islamic EducationIntellect is the greatest gift to humans as the best creation and as a differentiator from other creatures. The phenomenon in this era is that many people misuse their intellect and intelligence for bad things such as lying, stealing, corruption, and following mere lust. This paper aims to restore the concept and function of reason in accordance with the guidance of the Qur’an and its relevance to the world of Islamic education. This research is a library research. The analysis obtained is that reason makes people think, reflect, distinguish between haq and vanity, right and wrong, and receive all kinds of information, all of which can be used in Islamic education as a mutual scientific benefit so as to create a better Islamic life order